Rocky Road: East Asian International Students‟ Experience of Adaptation to Critical Thinking Way of Learning at U.S. Universities - Hyun Jung Lee (Adult Education Research Conference, 2012)
This roundtable seeks to understand how Confucius-influenced East Asian international students learn to adapt to and participate in the countervailing Western pedagogy that fosters independent critical thinking and reflection and how these Asian students reconcile these seeming polarities as they engage in their doctoral studies at U.S. universities.
Keywords: Confucian Philosophy; Critical thinking /reflection; East Asian students